(untitled) - Topolcany, Roman (Doprava a spoje, 2012)
The possibility to flight IFR in low altitudes over the territory of the Slovak Republic with nonpressure aircraft, which is fully equipped for IFR flight in accordance with applicable legislation, is currently limited. University of Zilina has installed recently in all aircrafts transponder mode A/C or S, depending on the requirements of current legislation over the territory of which the flight takes place. At the same time as a result of the project Centre of Excellence for Air Transport ITMS 26220120065, University of Zilina has installed system PCAS XRX ONYX, which appears to be suitable to increase safety of research mission.